Mapping the Levels of English Storytelling of Tour Guides in Jajar Gumregah Tourist Village Trenggalek - Dwi Wahyuningtyas; Laksmi , Diana; Dian Sasmitha i Dwi Maharani; Azzahra Yurenaudia; Yudiana Indriastuti (UIBU, 2023)
Storytelling is part of an adequate tourism promotion. Storytelling can describe a place, a tradition, a culture, and many other things that become tourist attractions. Storytelling is needed to promote tourism in Indonesia, including tourist villages. Tourist villages in Indonesia are part of tourism development in Indonesia. This study then analyzes and map the level of tour guides’ storytelling skill in Desa Wisata Jajar Gumregah Trenggalek. Seven participants were involved in this study by presenting their storytelling and were assessed by the researchers using some assessment criteria: pronunciation, fluency, comprehension, grammar, and expressions. Descriptive qualitative research design was employed in this study. The results indicated various levels of tour guides' storytelling skill, which is influenced by some factors. They are educational background, environment, confidence, and frequency of practice